Exploring the Attitudes and Practices of Pharmacists and Physicians towards Bush Medicine in Guyana - Ede Tyrell; Karishma Jeeboo; Jewel Edmonson-Carter; Troy Thomas; Rajini Kurup (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Aims: To examine the attitudes and practices of physicians and pharmacists towards bush medicine (including personal use) and explore the factors influencing their attitudes. Also, to determine whether a video educational intervention impacted attitudes. Introduction: The term ’bush medicine’ is used throughout the Caribbean to describe medicinal plants which are commonly used by traditional healers and is considered to be one aspect of traditional medicine. Study Design: This was a cross-sectional study of registered physicians and pharmacists. Place and Duration of Study: A total of 274 persons participated: 134 pharmacists attending their first Continuing Pharmacy Education (CPE) of 2015 and 140 physicians attending their annual Medical Scientific Conference. Methodology: A pre-tested, self-administered questionnaire was distributed and collected, a video intervention was shown, and a post-intervention questionnaire was administered. Data were analysed using latent class cluster analysis, and the best-fitting model was determined using mainly the Bayesian Information Criterion (BIC). Logistic and multinomial regression and Fisher’s exact test were also employed to investigate associations with demographic variables and the impact of the intervention. Results: Most of the participants (56.4%) were 20-30 years old, and the majority (52%) had five years or less professional experience. Pharmacists displayed a more positive attitude to bush medicine than physicians. Most (99%) believed that patients should inform their physician/pharmacist about their bush medicine use, but only 53% routinely requested this information. More than half (52%) had personally used bush medicine, but only 38% had ever recommended its use. More than 90% believed that clinical trials should be conducted with bush medicine before it is used, and 88% were interested in further training. Ethnicity, years of professional experience and type of profession influenced attitudes and the intervention led to an improved outlook regarding bush medicine. Conclusion: Overall, most participants had some misgivings about bush medicine but were willing to learn more and were interested in clinical trials. Evidence-based clinical research and training at the tertiary level or future continuing education sessions should be implemented using the content in the video as a template.